2020
DOI: 10.1136/tobaccocontrol-2019-055488
|View full text |Cite
|
Sign up to set email alerts
|

IQOS debut in the USA: Philip Morris International’s heated tobacco device introduced in Atlanta, Georgia

Abstract: Competing interests None declared. patient consent for publication Not required. provenance and peer review Not commissioned; externally peer reviewed. data availability statement There are no data in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 11 publications
2
47
0
Order By: Relevance
“…20) The United States Food and Drug Administration also permitted the sale of IQOS through the premarket tobacco product application on April 30, 2019, and PMI introduced IQOS in Atlanta, Georgia in October 2019. 21) In June 2017, PMI began selling IQOS in Korea and sold approximately two million IQOS devices within a year. 22) Given that novel tobacco products have attracted attention from smokers, British American Tobacco and KT&G Corporation also launched similar products-Glo in August 2017 and Lil in November 2017, respectively-in South Korea.…”
Section: The Advent Of Heated Tobacco Products In South Koreamentioning
confidence: 99%
See 1 more Smart Citation
“…20) The United States Food and Drug Administration also permitted the sale of IQOS through the premarket tobacco product application on April 30, 2019, and PMI introduced IQOS in Atlanta, Georgia in October 2019. 21) In June 2017, PMI began selling IQOS in Korea and sold approximately two million IQOS devices within a year. 22) Given that novel tobacco products have attracted attention from smokers, British American Tobacco and KT&G Corporation also launched similar products-Glo in August 2017 and Lil in November 2017, respectively-in South Korea.…”
Section: The Advent Of Heated Tobacco Products In South Koreamentioning
confidence: 99%
“…As of May 2020, IQOS is being testmarketed in more than 50 countries [ 20 ]. The United States Food and Drug Administration also permitted the sale of IQOS through the premarket tobacco product application on April 30, 2019, and PMI introduced IQOS in Atlanta, Georgia in October 2019 [ 21 ].…”
Section: The Advent Of Heated Tobacco Products In South Koreamentioning
confidence: 99%
“…Meanwhile, due to concerns from the E-cigarettes, or vaping, product use-associated lung injury (EVALI) outbreak, the Korean government encouraged e-cigarette users to stop using these products, resulting in existing vapers choosing conventional cigarettes or HTPs instead and an opportunity to expand the HTPs market. HTPs shall expand to the rest of the United States (US) within a few years if sales in the Atlanta test market go well [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that in the year 2018 alone tobac- products showed that some part of the general public associated the use of HTPs with wealthy people (the cost of using these devices is higher than that of smoking regular cigarettes) or people searching for new experiences [49]. What matters here is the marketing strategy of companies manufacturing HTDs, which promote free-of-charge or inexpensive training sessions in shops or offer starter packages at discount prices [50]. The fashionable looks of an IQOS device, which resembles a pen and draws on the cutting-edge technologies, induces young people to reach for this product.…”
Section: The Hazardous Phenomenon Of Tobacco Heating Productsmentioning
confidence: 99%